Application of Realia Media in Improving Student Learning Outcomes at Madrasah Ibtidaiyah - Wildah Al Aluf; Sulissatul Hasanah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Jember, 2022)
Using realia media in learning activities will provide an interesting learning experience for students so that they are more active in participating in learning. This discussion aims to describe and analyze the application of realia media in improving student learning outcomes at MIMA 35 Nurul Ulum Jember. The research approach uses qualitative and case study research types. Data collection techniques using observation, interviews, and documentation. Analysis of the data used in this study using the Miles and Huberman model consisting of data condensation, data presentation, and concluding. The validity of the data was tested by using triangulation of sources and techniques. The results of this study indicate (1) Realia media planning in improving student learning outcomes at MIMA 35 Nurul Ulum Jember, namely: Identifying the needs and characteristics of students, formulating learning objectives, summarizing material, writing instructional media scripts, conducting tests and revisions. (2) The implementation of realia media in improving student learning outcomes at MIMA 35 Nurul Ulum Jember, namely: the teacher learns the instructions for using the media, and all equipment must be in a state of readiness so as not to be disturbed by technical matters, and keep students steady. conducive for learning activities to take place. (3) Evaluation of realia media in improving student learning outcomes at MIMA 35 Nurul Ulum Jember, namely: learning media according to KD and indicators, learning media according to the estimated time and assignments in the Buena book, learning media can attract students' attention, media learning is in accordance with the times/updated, thematic assessment criteria are spiritual, social, knowledge, and skillful. Penggunaan media realia dalam kegiatan pembelajaran akan memberikan pengalaman belajar yang menarik bagi peserta didik sehingga lebih aktif dalam mengikuti pembelajaran. Pembahasan ini bertujuan mendeskripsikan dan menganalisis tentang Penerapan media realia dalam meningkatkan hasil belajar peserta didik di MIMA 35 Nurul Ulum Jember. Pendekatan penelitian menggunakan kualitatif dan jenis penelitian studi kasus. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Analisis data yang digunakan dalam penelitian ini menggunakan model Miles dan Huberman yang terdiri dari kondensasi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diuji dengan menggunakan triangulasi sumber dan teknik. Hasil penelitian ini menunjukkan: (1) Perencanaan media realia dalam meningkatkan hasil belajar peserta didik di MIMA 35 Nurul Ulum Jember, yaitu: Mengidentifikasi kebutuhan dan karakteristik peserta didik, merumuskan tujuan pembelajaran, membuat rangkuman materi, menulis naskah media pembelajaran, mengadakan tes dan revisi. (2) Pelaksanaan media realia dalam meningkatkan hasil belajar peserta didik di MIMA 35 Nurul Ulum Jember, yaitu: guru mempelajari petunjuk penggunaan media, seluruh peralatan harus dalam keadaan siap agar tidak terganggu oleh hal-hal yang bersifat teknis, dan menjaga agar peserta didik tetap kondusif selama kegitan pembelajaran berlangsung. (3) Evaluasi media realia dalam meningkatkan hasil belajar peserta didik di MIMA 35 Nurul Ulum Jember, yaitu: media pembelajaran sesuai dengan KD dan indikator, media pembelajaran sesuai dengan estimasi waktu dan tugas dalam buku Bupena, media pembelajaran dapat menarik perhatian peserta didik, media pembelajaran sudah sesuai dengan perkembangan zaman / terupdate, kriteria penilaian Tematik yakni spiritual, sosial, pengetahuan, dan keterampilan.